1985
DOI: 10.1007/bf00383545
|View full text |Cite
|
Sign up to set email alerts
|

1-Hydroxypyrene in human urine after exposure to coal tar and a coal tar derived product

Abstract: A method for isolating 1-hydroxypyrene from urine is described. The presence of 1-hydroxypyrene in urine was identified by fluorescence excitation and emission scanning after HPLC-separation. 1-Hydroxypyrene could be detected in the urine of rats following oral administration of as little as 0.5 microgram pyrene. The dose-dependence of 1-hydroxypyrene in urine was evident after a wide range of pyrene dosing. After therapeutical coal tar treatment of dermatological patients the enhanced excretion of 1-hydroxypy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(91 citation statements)
references
References 9 publications
2
80
0
4
Order By: Relevance
“…Among these, urinary metabolites 1-OHP and 2-naphthol have served as good biomonitoring markers (Jongeneelen et al, 1985;Kim et al, 1999). In our present study, the urinary 1-OHP and 2-naphthol concentration in both subjects were found to be similar to those in aircraft maintenance and shipyard workers Lee et al, 2001).…”
Section: Discussionsupporting
confidence: 71%
“…Among these, urinary metabolites 1-OHP and 2-naphthol have served as good biomonitoring markers (Jongeneelen et al, 1985;Kim et al, 1999). In our present study, the urinary 1-OHP and 2-naphthol concentration in both subjects were found to be similar to those in aircraft maintenance and shipyard workers Lee et al, 2001).…”
Section: Discussionsupporting
confidence: 71%
“…The analytic procedure to determine urinary 1-OHP levels using reverse-phase highperformance liquid chromatography with fluorescence detection has been described previously (16,24,25). Reported levels of 1-OHP are the sum of the free compounds and the sulfate and glucuronide conjugates.…”
Section: Methodsmentioning
confidence: 99%
“…The level of 1-OHP in urine was determined using reverse-phase high performance liquid chromatography (HPLC) after a modification of the method of Jongeneelen et al 33) . Ten milliliters of thawed urine were adjusted to pH 5.0 with 1.0 N acetic acid, 10 ml of 0.1 M sodium acetate buffer (pH 5.0) was added and the mixture was enzymatically deconjuated by 25 µl of β-glucuronidase/ sulfatase (127,300 units/ml and 7,500 units/ml).…”
Section: Determination Of 1-hydroxypyrene In Urinementioning
confidence: 99%